Effect Mechanism of Error Management Climate on Innovation Behavior: An Investigation From Chinese Entrepreneurs - Chen, Yuting; Wei, Jiangru; Zhang, Jing; Li, Xue (Frontiers in Psychology, 2021)
Errors are inevitable in an increasingly risky and dynamic entrepreneurial environment. The error management and the error climate perceived by the members are crucial to the subsequent innovation behaviors. Maintaining and improving the psychological capital of entrepreneurs under errors is not only the psychological activities of entrepreneurs themselves but also a critical management process in which an organization can influence the psychological factors and behaviors of entrepreneurs through error management climate. In the context of Chinese culture, this study explores the influence of error management climate on entrepreneurial self-efficacy and innovation behavior under the boundary condition of Zhongyong thinking. Two hundred ninety samples of Chinese entrepreneurs are empirically analyzed in this study, and results show that: (1) error management climate and entrepreneurial self-efficacy have significant positive effects on entrepreneurs’ innovation behavior; (2) entrepreneurial self-efficacy mediates the relationship between error management climate and innovation behavior; (3) Zhongyong thinking plays moderating roles in the process of error management climate influencing innovation behavior. This study complements the entrepreneurship literature with its focus on error management climate as an essential antecedent of entrepreneurial self-efficacy, and promotes an understanding of how Chinese practitioners promote innovative behavior from a cultural perspective.